The Art of Invisibility: The World's Most Famous Hacker Teaches You How to Be Safe in the Age of Big Brother and Big Data - Kevin D. Mitnick; Robert Vamosi (New York Back Bay Books, 2021)
Your every step online is being tracked and stored, and your identity easily stolen. Big companies and big governments want to know and exploit what you do, and privacy is a luxury few can afford or understand. In this explosive yet practical book, computer-security expert Kevin Mitnick uses true-life stories to show exactly what is happening without your knowledge, and teaches you "the art of invisibility": online and everyday tactics to protect you and your family, using easy step-by-step instructions. Reading this book, you will learn everything from password protection and smart Wi-Fi usage to advanced techniques designed to maximize your anonymity. Invisibility isn't just for superheroes--privacy is a power you deserve and need in the age of Big Brother and Big Data.
Keywords: Computer Science; Hackers; Nonfiction; Science; Technology